Surface properties of impregnated and varnished Scots pine wood after accelerated weathering - Baysal, Ergun; Dizman Tomak, Eylem; Ozbey, Musa; Altin, Ebedin (Wiley, 2014)
In this study, the effect of accelerated weathering on the surface properties of Scots pine specimens impregnated with wolmanit-CB, tanalith-E, and adolit-KD5 and coated with synthetic and polyurethane varnishes was investigated by measuring surface hardness, glossiness, and colour. Results showed that weathering caused an increase in the hardness of impregnated and varnished specimens, while it caused a decrease in the glossiness of specimens. Surfaces became rougher and darker after weathering in comparison with the initial surfaces of wood specimens. Positive values of the chromatic coordinates indicated that the wood surfaces changed from their original colour to a reddish and yellowish colour. The highest colour change was detected in the specimens coated with polyurethane varnish alone. Both copper-based wood preservative treatment and varnish coating improved the surface properties of specimens in comparison with the surface properties observed on specimens coated with varnish alone.
Keywords: [No Keywords]